Integration of Community Space and Design of Educational Space under Child Friendly Concept - Ren, Xiangxin; Zhang, Yimeng; Zhang, Haoran (Journal of Research in Science and Engineering, 2026)
Starting from the integration of children’s educational space and community public space, this article takes Xiangdong Community in Beijing as a case for design practice research. It aims to construct a child-friendly community space system and promote the realization of a child-friendly community. Through a literature review and case analysis, the study reviews domestic and international practices. It then selects Xiangdong Community in Beijing and, guided by child development theory and space-sharing theory, develops a spatial integration design strategy centered on a vertical core and horizontal connections. The study provides a systematic and objective analysis of the relationships among multiple complex stakeholders in the community. It represents a proactive attempt to build a child-friendly community, improving the quality of children’s growth environments and the overall level of community development.